Given
f(x)= -3x - 5
g(x)= 4x - 2
Find
(f - g)(x)
substitute the f and g values in (f - g)
(f - g)(x)= -3x - 5 - (4x - 2)
change the signs in parentheses because there is a negative sign in front of the parentheses
(f - g)(x)= -3x - 5 - 4x + 2
combine like terms
(f - g)(x)= -7x - 3
ANSWER: (f - g)(x)= -7x - 3
Hope this helps! :)
Answer:
13
Step-by-step explanation:
(6-4=2)
8+2 +3
8+2=10
10+3=13
=13
This is question of geometric sequence, equation of growth for this matter. The explicit formula for geometric sequence is given by:
a(n) = a(0)r^(n-1)
where;
a(n) = population after time "n"
a(0) = Initial population = 65
n = time = 5 weeks
r = common ratio = (100+30)% = 1.3
Substituting, beetles after 5 weeks will be;
a(5) = 65*1.3^(5-1) = 185.65 ≈ 186 beetles